Improved removal of Cd(II) from aqueous solution by synthesized nanozeolite. Issue 60 (25th December 2016) - Pham, Thi-Huong; Lee, Byeong-Kyu; Kim, Jitae; Lee, Chi-Hyeon
Abstract: This study investigated the adsorption potential of synthesized nanozeolites for the removal of cadmium (Cd(II)) ions from aqueous solutions. The obtained adsorption results for Cd(II) removal indicate that the nanozeolites had higher surface area, pore volume, and adsorption capacity than commercial activated carbon (AC). The synthesized nanozeolites were well fitted with the Langmuir adsorption isotherm and the second-order reaction kinetic. Based on the Langmuir model, the maximum adsorption capacities of Cd(II) onto nanozeolite and AC were 189.6 and 171.2 mg/g at an optimum pH of 5.0, respectively. In the regeneration study of Cd(II)-loaded adsorbents, even after 10 cycles of adsorption–desorption, the identified desorption efficiencies of Cd(II) were 78.8 and 42.3% using nanozeolites and AC, respectively. Based on the adsorption characteristics of Cd(II), the synthesized nanozeolites could be utilized as a promising low-cost adsorbent for Cd(II) removal from water.